Morphological features, distribution and ecological preferences of Albertiniella polyporicola (Jacz.) Malloch et Cain (CHORNOMORSKI BOTANICAL JOURNAL, 2013)
Based on the holotype review, own materials and literature in the article data about the distribution and ecological features of rare species of fungicolous fungi – Albertiniella polyporicola (Jacz.) Malloch et Cain are summarized. The history of this species study, the complete nomenclatural characteristics, revised description and original illustrations are presented. At the first time it is reported about finding of A. polyporicola on the basidiomata of Ganoderma resinaceum Boud.
Keywords: Albertiniella polyporicola, Ganoderma, fungicolous fungi, Ukraine.